The Historical Evolution of Qawaid Fiqhiyyah and Its Relevance as a Legal Maxim in the Perspective of General Law - Purnama Wahyuni; Habib Al-Rabith Naslim (AT-TAFAHUM: Journal of Law, 2019)
The principles of Islamic jurisprudence (Qawa'id Fiqhiyyah) play a crucial role as guidelines for Islamic law in addressing various contemporary issues amidst the limited number of texts of the Qur'an and Sunnah quantitatively. This study aims to examine the period of formation and development of the principles of Islamic jurisprudence and analyze their relationship with the concept of *legal maxim in the context of general law. Through literature study, it was found that the development of the principles of Islamic jurisprudence is divided into three main periods: the birth period (the time of the Prophet, Companions, and Tabi'in), the codification period (4th century AH to the golden age in the 8th century AH), and the refinement period culminating in the compilation of Majallat Al-Ahkam Al-Adliyyah in the 13th century AH. The analysis shows a strong relevance between the basic principles of Islamic jurisprudence and general legal principles, such as the relationship between the principle of "Al-umur bi maqasidiha" and the concept of mens rea in criminal law, and the principle of "Al-yaqin la yuzal bi asy-syakk" with the principle of proof in court. The research results conclude that the rules of Islamic jurisprudence function as legal maxims that provide a universal framework for legal practitioners in resolving disputes and formulating legal norms.